2014
DOI: 10.1002/app.40630
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and functional evaluation of agarose derivatives

Abstract: A facile microwave‐assisted one‐pot synthesis of sodium carboxymethylagarose and calcium carboxymethylagarose from Gracilaria dura agarose (Ag) has been described. The process is user friendly, and the highest degree of substitution was obtained within 15 min compared with the conventional method, which requires more than 3 h. Solubility and gelling behavior of the modified Ag products were found to be dependent on degree of substitution of the products. The characterizations were done by using Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The amylose-to-amylopectin ratio can influence the properties of the biobased materials. It is reported that amylose-rich materials are preferred because they show better thermal stability, superior strength, and lower water absorption than amylopectinrich materials [4][5][6]. In this study, the starch-containing agricultural waste had a lower amylose content than normal native starch, even as low as only 1% amylose, with the remainder being amylopectin.…”
Section: Introductionmentioning
confidence: 68%
“…The amylose-to-amylopectin ratio can influence the properties of the biobased materials. It is reported that amylose-rich materials are preferred because they show better thermal stability, superior strength, and lower water absorption than amylopectinrich materials [4][5][6]. In this study, the starch-containing agricultural waste had a lower amylose content than normal native starch, even as low as only 1% amylose, with the remainder being amylopectin.…”
Section: Introductionmentioning
confidence: 68%
“…The results depict that, at such a ratio of polymers of AG, sustainability in drug release was not achieved and showed a poor release retardant effect. This might be due to the fact that AG possesses weak hydrophilic forces in powder form [44], while PVP, the hydrophilic polymer, did not impart the required results with the release of both drugs, and the tablets diminished completely after 2 h of sampling. Consequently, the drugs dissolute with a faster release from eroded matrix [45].…”
Section: Dissolution Studymentioning
confidence: 98%
“…CMA was synthesized from seaweed polysaccharide agar extracted from Gracilaria edulis using a previously reported method (with high DS) 25 . Sodium hydroxide and isopropyl alcohol were purchased from Thermo Fisher Scientific India Pvt Ltd. Metal (lithium, mercury, arsenic, cadmium, rubidium, chromium, copper, cobalt, strontium, zinc, magnesium and nickel) ions (perchlorate salts) were purchased from Alfa Aesar.…”
Section: Methodsmentioning
confidence: 99%